MODELING AND IMPACT ANALYSIS OF LAND SUBSIDE TO THE PHENOMENON OF FLOODING IN JAKARTA - YUHANAFIA (NIM : 25114010), NURUL
Land subsidence and flooding are a natural phenomenon that usually occurs in Jakarta and continues until today. Both of these natural phenomenon are interrelated to each other, but the research that included land subsidence as a variable in flood research in Jakarta is still rare. This study and analysis was conducted to prove the effect of land subsidence on the increased of flooding that occurred by using a flood modelling. Modeling was performed using SOBEK software by creating a flood scenario in Jakarta. The result of this research is a flood map that has a flood depth value from the year of 2002, 2007, 2012, 2017, 2022 and 2027. The results of the flood area expansion on each map are compared with the year of 1975 and 2007 floods results map. The map shows that flood area expansion increase to 116 percent in the period 1975 to 2002, and continues to 315 percent in 2027. Also, by the year of 2007 until 2027 (20 years), flood area expansion increases to 64 percent. The expansion of flood causes an increment of economic losses too. In 2027, the estimated value of the economic losses increase to 36 trillion or 73% from 20 trillion in 2007, as a result of the expansion of floods due to land subsidence.